Professor M.S. Pavgi Lecture - Current Status of Rice Blast in India and Challenges Ahead - SINGH, R.A. (Indian Phytopathology, 2002)
The nomenclature, host range, cytology and disease management of the rice blast pathogen, Magnaporthe grisea, are briefly discussed. The current status of the disease in India and future challenges are also presented.